DIPG-04. THERAPEUTIC STRATEGY FOR DIFFUSE MIDLINE GLIOMAS. A SINGLE CENTER EXPERIENCE. (4th December 2020) - Yamanaka, Takumi; Takahashi, Yoshinobu; Morisako, Tamaki; Nagai, Toshiki; Tanigawa, Seisuke; Umebayashi, Daisuke; Takeuchi, Hayato; Tatsuzawa, Kazunori; Miyachi, Mitsuru; Yagyu, Shigeki; Iehara, Tomoko; Hosoi, Hajime; et al.
Abstract: INTRODUCTION: Diffuse midline gliomas have unfavorable prognoses due to the difficulty of surgery and chemo-radiation resistances. The purpose of this study is to overview our surgical experiences and prognoses of this challenging neoplasm. MATERIALS AND METHODS: Five patients of diffuse midline gliomas who were treated between 2016 and 2019 were enrolled. Tumor locations, surgical procedures, molecular diagnoses, and prognoses were retrospectively reviewed. RESULTS: There were 3 male and 2 female patients, and the median age was 15 years ranged from 7 to 21 years. Tumors were located at the basal ganglia in 1 patient, thalamus in 1, brain stem in 2, and cervical spine in 1. Mutations of H3 K27M genes were detected in 4 surgically treated patients, except for 1 patient, who were radiologically diagnosed as diffuse intrinsic pontine glioma (DIPG). Focal irradiation of ranged 35 to 54Gy were administered in all cases along with temozolomide in 2 cases and bevacizumab in 2 cases. The median survival time was 13 months ranged from 4 to 18 months. DISCUSSION: Supratentorial tumors were maximumly resected, whereas just biopsies were performed in cases of exophytic brain stem and spinal tumors. Diagnosis of DIPG was made without using surgical specimens. Therapeutic strategies should be discussed with a concern to the patients' qualities of life for this tumor entity with dismal prognosis.